Women on the Board and the Impacts on Executive Compensation and Performance of Large Brazilian Companies - Iglesias, Thayla Machado Guimarães; Guimarães, Thayse Machado; Rogers, Pablo (Advances in Scientific and Applied Accounting, 2024)
Goal: This study aims to investigate the influence of gender diversity on the board of directors on the large Brazilian companies’ economic-financial performance and executive compensation. Method: We analyzed 84 non-financial companies from the IBrX 100, using a dynamic panel (2015 to 2019) with GMM System in one and two stages. Results or Discussion: The main evidence indicated that gender diversity did not provide economic benefits, either by improving economic-financial performance or by reducing managers’ excessive compensation, which, therefore, shows that the hypotheses were not answered. Despite the findings, we emphasize that companies must make efforts to ensure that the gender quota policy within the entity is implemented above the minimum, not restricted to the percentage established by law. Such action inspires credibility among stakeholders, as it highlights the institution’s commitment to diversity. Contributions: The gender diversity discussion is pertinent, especially in the Brazilian reality, where female representation in large organizations is small (10%), only with 53% of companies having at least one woman on their boards of directors. In emerging countries like Brazil, discussions regarding diversity are still incipient, notably because there is no consolidated legislation on the subject, other than a bill awaiting voting and deliberation. Then it configures this study’s innovation, which is normally found in developed countries.